Alfabetização na perspectiva do letramento na educação de pessoas jovens, adultas e idosas no município de Dois Vizinhos-PR - Skorek, Cenira Rosa Cechin (2020)
Current literacy conditions require the training of people who know, in addition to reading and writing, how to make competent use of these skills according to social demands. Consequently, learning to read and write is not enough, it is necessary to go beyond functional literacy. In this sense, we sought to understand the literacy process from the perspective of literacy in an EJA class. Thus, the present research questions: How does the process of literacy and literacy occur in the Education of Young, Adult and Elderly People in the municipality of Dois Vizinhos-PR? In view of this problem, the objective was to understand how the literacy process occurs from the perspective of literacy with these students in the EJA of that municipality, investigating literacy and literacy practices and the impacts of schooling on the lives of these subjects. To achieve the central objective and answer the research question, the following specific objectives are established: a) to place the Education of Young, Adult and Elderly People in the context of legal rights and public policies on literacy in Brazil; b) discuss the conceptual aspects of literacy and literacy relating them to the context of EJA; c) reflect on the context of literacy and literacy in EJA and the contributions of popular education with a Freirian conception in dialogue with the conception of historical-cultural theory for schooling these students; d) present a proposal for pedagogical intervention in order to socialize the results of the research with the Municipal Education Secretariat of the municipality of Dois Vizinhos-PR. The theoretical-methodological foundation was based on the liberating, establishing a dialogue with the historical-cultural perspective and scholars of these areas of knowledge, following the example of Freire (1997, 2001, 2002, 2003); Brandão (1981, 2012); Gadotti (2009) and Pinto (1987), about the concept of education; popular education; emancipation and humanization and Vygotsky (1989, 2007, 2016); Oliveira (1999, 2001, 2008) and Rego (1995) with respect to historical-cultural theory. On EJA throughout the history of education in Brazil in aspects such as rights and public policies, Paiva (2015); Haddad (2000); Di Pierro (2010), Soares (2011); Arroyo (2011, 2016, 2017). In interlocution with these authors and for a better understanding of this singular public that frequents EJA, support was sought in the studies of Laffin (2013); Oliveira (1992, 1999); Losso (2012) and Sanceverino (2016). The theoretical contributions that guided the studies on literacy from the perspective of literacy were found in Soares (1998, 2000,2003); Tfouni (1998, 2004, 2006); Ribeiro (2003); Kleiman (1995), among others. The research methodology adopted is the qualitative approach (Ludke; André, 2017) of the exploratory research type (Gil, 2007). First, a bibliographic research was carried out, of the state of knowledge type and as instruments of data collection, analyzes of the literacy teacher class diary were used, as well as semi-structured interviews (GIL, 2007) with students and the class teacher. The data were analyzed following the techniques of Content Analysis (Bardin, 1977). The results show that the teacher seeks to contemplate the challenges of EJA, promoting literacy in the perspective of literacy. They also point out some findings and needs, among them, the importance of recognizing the knowledge (Charlot, 2000) of the students and the teacher from the mediations to meet the specificities of EJA, which requires specific methodologies and demand training of ( the teacher). It should also be noted that EJA is a modality of Basic Education with public policies still insufficient to meet the needs of this public and, really, end illiteracy.